Ficção e recognição: Mia Couto e o discurso da experiência uma análise sob a perspectiva da linguística de corpus - Lima, Amauri de (2018)
This research consists of the study of the works Sleepwalking Land (1992), The Last Flight of the Flamingo (2000) and The Tuner of Silences (2009) by the Mozambican author Mia Couto. The proposal was based on the comparative analysis of the works from the perspective of Corpus Linguistics, whose methodology used the WordSmith Tools 6.0 software, to select keywords of the study corpus in comparison with a corpus of reference of Brazilian Portuguese. The aim of the analysis is to understand how the works interact with each other, so that it is possible to grasp the literary fact as mise-en-texte of social discourses, that is, how the different discourses in circulation materialize in the literary text. The organized theoretical basis took into account the Literary Theory, Cultural and Postcolonial Studies, besides a Sociocritical base. From the study, the words: ground / floor, voice and old were written as keywords, which in a general way, organize the themes that make up the fictional construction of Mia Couto in the selected works. The investigation of data gathered in a quantitative-qualitative way and obtained semiautomatically, through computerized resources, allowed a unique approach on the discourse strategies of Mia Couto, considering the options and tendencies presented in front of words that represent typical elements of the culture and identity of Mozambican and writing in Portuguese. The highlighted words reflect cultural hybridity and value the manifestation of the divergent, the unusual, the heterogeneous, the contradictory. Mia Couto, referring to the land, the expressiveness and the memory of a nation, awakens universal tones for alterity and resistance, whose concepts are historically pursued by a significant part of humanity. The analysis of the words earth / ground, voice and old, indicates that the fiction of Mia Couto contributes to the appreciation of Africa as a multiethnic and multicultural space, strengthening the land, orality and ancestry as strategies to represent a nation.